Hepato- and Nephroprotective Effects of Ethanolic Extract of Seeds of Macrotyloma uniflorum on Paracetamol-induced Hepato- and Nephrotoxicity in Rats - Parasuraman, Subramani; Qi, Yap Zi; Jie, Loo Wei (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: The present study is planned to investigate the hepato- and nephroprotective effects of ethanolic extract of seeds of Macrotyloma uniflorum (EEMU) on paracetamol (PCM)-induced hepato- and nephrotoxicity in Sprague-Dawley rats. Materials and Methods: Hepato- and nephroprotective effects of EEMU were studied against PCMinduced hepatotoxicity and nephrotoxicity in rats. The rats were divided in to seven groups’ viz., control, EEMU 400 mg/kg, PCM, PCM + Vitamin C 200 mg/kg, PCM + EEMU 100 mg/kg, PCM + EEMU 200 mg/kg and PCM + EEMU 400 mg/kg. The animal in groups III to VII were administered with PCM (750 mg/kg) once daily for seven days to induce hepato- and nephrotoxicity. EEMU and Vitamin C were administered once daily per orally for 7 days. On day 8, the animals were anaesthetized and blood samples were collected and used for estimation of biochemical parameters. Later the animals were sacrificed and liver and kidney were collected from all the animals for antioxidant assay and histopathological analysis. Results: The animals administered with EEMU (400 mg/kg) didn’t show any significant changes in the biochemical parameters and histological features. The animals administered with PCM showed a significant increase in the levels of AST, ALT, ALP, bilirubin and urea compared with that of the control group. Whereas the animals administered with Vitamin C and EEMU (at 200 and 400 mg/kg) prevented PCM-induced changes in biochemical parameters and histological features. In the antioxidant assay, the animals administered with EEMU, PCM + Vitamin C and PCM + EEMU 400 mg/kg, didn’t show any significant changes in the levels of reduced glutathione when compared with that of the control group. Conclusion: EEMU exhibited a significant hepatoprotective effect at the dose levels of 100, 200 and 400 mg/kg against PCM-induced hepatotoxicity in rats. EEMU did not show any significant nephroprotective effect at the same dose levels on PCM-induced nephrotoxicity in rats.
Keywords: Medical herbs; Nutrition; Hepatic injury; Renal failure; Toxicity